2017
DOI: 10.1021/acs.cgd.7b00664
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Hydrate Screening: Cytosine, 5-Flucytosine, and Their Solid Solution

Abstract: The structural, temperature- and moisture dependent stability features of cytosine and 5-flucytosine monohydrates, two pharmaceutically important compounds, were rationalized using complementary experimental and computational approaches. Moisture sorption/desorption, water activity, thermal analysis and calorimetry were applied to determine the stability ranges of hydrate ↔ anhydrate systems, while X-ray diffraction, IR spectroscopy and crystal structure prediction provided the molecular level understanding. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 89 publications
1
35
0
Order By: Relevance
“…1), we reported a monohydrate solid solution of these two substances. Preliminary dehydration studies of this monohydrate indicated the formation of two distinct solid forms with powder X-ray diffraction and IR spectroscopy data showing structural resemblance with the data of the two known 5-flucytosine anhydrates 30. This observation motivated us to take a closer look at the existence of isomorphic phases and isopolymorphs in this binary system.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…1), we reported a monohydrate solid solution of these two substances. Preliminary dehydration studies of this monohydrate indicated the formation of two distinct solid forms with powder X-ray diffraction and IR spectroscopy data showing structural resemblance with the data of the two known 5-flucytosine anhydrates 30. This observation motivated us to take a closer look at the existence of isomorphic phases and isopolymorphs in this binary system.…”
mentioning
confidence: 71%
“…Also, 5-flucytosine shows anhydrate polymorphism ( F-I : MEBQEQ01 (ref. 41) and F-II : MEBQEQ41) and a rich solvate/hydrate crystal form landscape: hemihydrate,42 two monohydrates,41 hemipentahydrate41 and six solvates (methanol,41 ethanol,30 2,2,2-trifluoroethanol,41 dimethyl acetamide,42 dimethyl sulfoxide42 and dimethyl formamide30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The lengths of the hydrogen bonds between the C ketone groups and the hydrogen atoms of water molecules were 1.781 Å for O1⋯H21-O5 and 1.735 Å for O1⋯H27-O7. The C-MH hydrogen bonds were stronger and more abundant than those of C, which leads to different intermolecular interactions of C molecules and a more stable crystal structure with new cell parameters, i.e., the co-crystallization process 12,44 . Also, a change in the molecule's environment and conformation leads to a characteristic change in the THz spectra.…”
Section: Results Thz Absorption Spectra Of C and C-mh The Experimentmentioning
confidence: 99%
“…The above strategy has been deployed successfully in the blind tests and in the prediction of the crystal structures of pharmaceutically relevant molecules (Braun et al, 2016(Braun et al, , 2017Price et al, 2016). However, in view of the need to tackle ever larger and more flexible molecules of pharmaceutical interest, further improvements to the efficiency of the algorithms are required.…”
Section: Introductionmentioning
confidence: 99%